The Effect Of Delta Buying Options In The Profitability Of The Original Basis. Applied Research On The Company Of Apple Phones And Communication Technology - Hadi Abdulameer, Hussein; Abbas Al-janabi, Haider (Opción, 2019)
The derivatives market is considered as one of the cornerstones of the financial markets, since the establishing of financial options market in 1973 the financial markets have entered a new era and a new turn. According to these great changes, which are created by derivatives in the financial world and financial markets, therefore, ‘’Financial Options’’ started to take its primary place among securities which are playing an important role in the accounts of investors, speculators, and traders in the financial markets. In addition to the entering of options as a basic player to protect investors’ money losses through the use of options as a facet of hedging and preserving the wealth and the fi- nancial centres of these dealers. The study deals with highlighting the Delta Options which concerned with the options of buying and their roles in the level of profits that is achieved by original basis. Additionally, it aims to discover whether these Delta options have a primary or secondary role in attracting investors to invest in the original basis. Moreover, the study aims to show the level of the relationship between the bonus buying options and the price of the original basis by accounting Delta Options.